2014
DOI: 10.1002/pat.3346
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and properties of cyanate Ester/nanodiamond composites

Abstract: The aim of this study was to improve thermal conductivity, thermal stability, and mechanical properties of bisphenol A dicyanate ester with the addition of nanodiamond. Cyanate ester/nanodiamond composites containing various ratios of nanodiamond were prepared. Thermal stability and thermal conductivity of the samples were evaluated by thermogravimetric analysis, differential scanning calorimetry, and laser flash method, respectively. The samples were characterized with the analysis such as gel content, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Cyanate esters have attracted considerable attention due to their unique properties such as low water absorption, low dielectric constant and heat release rate, good strength, excellent adhesion to metals, glass, and carbon fibers, low out gassing in curing and high environment resistance . Because of these properties, cyanate ester‐based resins have been widely used as adhesives and matrixes for composites.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanate esters have attracted considerable attention due to their unique properties such as low water absorption, low dielectric constant and heat release rate, good strength, excellent adhesion to metals, glass, and carbon fibers, low out gassing in curing and high environment resistance . Because of these properties, cyanate ester‐based resins have been widely used as adhesives and matrixes for composites.…”
Section: Introductionmentioning
confidence: 99%
“…The second, between 270 and 470°C, is attributed to thermal degradation of the polymer main chain. Results show that the temperature corresponding to 50 wt% loss of samples were increased about 28°C with the addition of 2% nonodiamond . It was determined that the residuals %weight of the all samples are about 1%.…”
Section: Resultsmentioning
confidence: 94%
“…Most of these publications were related to metallic matrix materials (Al, Cu, and Ag) . Up to now there have been a limited number of publications where diamond grains have been successfully introduced into the polymer matrix resulting in significant improvements in the matrix properties .…”
Section: Introductionmentioning
confidence: 99%
“…DSC results showed that the addition of cationic hydroxyethyl cellulose and sodium alginate increased the T g values of the samples. It could be because of 2 reasons: the increase in carboxylate segment concentration by increase of sodium alginate and the loss of mobility of polymer chains because of the decrease in free volume …”
Section: Resultsmentioning
confidence: 99%